Cloning of interleukin-10 gene in the Indian major carp, Labeo rohita (Hamilton 1822) and its functional characterization following Aeromonas hydrophila infection - Swain, B; Basu, M; Samanta, M (Indian Journal of Fisheries, 2012)
Interleukin-10 (IL-10) is a pleiotropic cytokine, expressed in various species of fish and higher vertebrates, and is activatedduring infection. In this report, we describe the identification and characterization of IL-10 in the Indian major carp (IMC),rohu (Labeo rohita), which is the most preferred and commercially important species in the Indian subcontinent. The rohuIL-10 cDNA consisted of 1103 bp nucleotides, having 65 bp and 495 bp un-translated regions at the 5’ and 3’ end respectively.The open reading frame consisted of 543 bases, encoding 180 amino acids with a putative signal peptide of 22 amino acids.Deduced amino acid sequence of rohu IL-10 showed highest similarity (97.8%) and identity (91.7%) with common carp(Cyprinus carpio) IL-10. Phylogenetic analysis indicated that the rohu IL-10 amino acid sequence resembles common carpIL-10, more closely related to silver carp (Hypophthalmichthys molitrix) and zebra fish (Danio rerio). Basal IL-10 expressionanalysis in ten different tissues of healthy fish by quantitative real-time PCR (qRT-PCR) assay showed its constitutiveexpressions among the tested tissues; with highest expression in the muscle, intestine and brain followed by gill, kidney andthe lowest expression in heart. Following Aeromonas hydrophila infection, IL-10 mRNA transcripts were analysed in gill,liver and kidney by qRT-PCR assay, and it showed significant induction (p